Efeitos do chumbo sobre a atividade da tioredoxina redutase citosólica (TrxR1) e parâmetros de estresse oxidativo em rins de ratos - Conterato, Greicy Michelle Marafiga (2007)
Lead is a heavy metal that accumulates primarily in kidney, where exerts its nephrotoxic effects. Several studies suggest that the oxidative stress is an important molecular mechanism for the toxic effects of lead in kidney and in other organs. Cytosolic thioredoxin reductase (TrxR1) is a selenoflavoprotein involved in many processes modulating intracellular reactive oxygen species levels. The aims of this study were to evaluate the effects of acute and chronic exposure to lead acetate on renal TrxR1 activity and on other oxidative stress parameters (d-aminolevulinic acid dehydratase activity, glutathione Stransferase, non-protein thiol groups, lipid peroxidation, and antioxidant enzymes in kidneys), as well as on plasmatic indicators of renal function (creatinine, uric acid and phosphate) in rats. In acute exposure, rats received a single intraperitoneal injection of 25 or 50 mg/kg lead acetate and were killed 6, 24 or 48 h later. In chronic exposure, rats received a daily intraperitoneal injection of lead acetate (5 or 25 mg/kg) during 30 days and were killed at 31st day. In our study, acute exposure to 25 mg/kg lead acetate increased superoxide dismutase (SOD) and TrxR-1 activity (after 6, 24, and 48 h), while exposure to 50 mg/kg lead acetate increased catalase (CAT) activity (after 48h) and inhibited d-aminolevulinic acid dehydratase (δ-ALA-D) activity (after 6, 24, and 48 hs) in kidneys (P < 0.05). Chronic exposure to 5 mg/kg lead acetate inhibited δ-ALA-D and increased glutathione S-transferase (GST), non protein sulfhydryl groups (NPSH), CAT, TrxR-1, and uric acid plasma levels, while exposure to 25 mg/kg lead acetate reduced body weight and δ -ALA-D, but increased GST, NPSH, and uric acid plasma levels (P < 0.05). No changes were observed in thiobarbituric acid reactive substances, glutathione peroxidase, creatinine or inorganic phosphate levels after either acute or chronic exposure. In conclusion, lead exposure caused a marked increase in the TrxR1 activity in the kidney of rats and this change may be an early indicator of acute exposure to low lead doses. However, further studies are needed to clarify the biological meaning of this induction as well as the mechanism involved in such effect.